1.3k views
2 votes
1. For the function f(x) = 3x + 1, find f(-2). (substitute -2 in for x)

1 Answer

6 votes

Answer:

f(-2) = -5

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

f(x) = 3x + 1

f(-2) is x = -2

Step 2: Evaluate

  1. Substitute in x: f(-2) = 3(-2) + 1
  2. Multiply: f(-2) = -6 + 1
  3. Add: f(-2) = -5
User Bogdan Stoica
by
5.7k points